A new species of the genus Borogonalia (Hemiptera: Cicadellidae: Cicadellinae) from Colombia and color pattern variations in B. impressifrons (Signoret, 1854) - Silva-Castaño, Andres Felipe; Dietrich, Christopher H. (Zootaxa, 2026)
One new species of the subfamily Cicadellinae (Hemiptera: Cicadellidae), Borogonalia wilsoni Dietrich & Silva-Castaño sp. nov. from Colombia is described. Also, color pattern variations found in Borogonalia impressifrons (Signoret, 1854) were analyzed. The new Colombian species is clearly distinguished from other Borogonalia species by the relatively pointed head and indistinct transverse concavity anterad of the ocelli.